Public Reporting of Corporate Financial Forecasts (Book). - Windal, Floyd W.; Spiller, Earl A. (The Accounting Review, 1975)
Reviews the book 'Public Reporting of Corporate Financial Forecasts,' edited by Prem Prakash and Alfred Rappaport.